The Relationship of Succession Planning, Career Attitude and Job Security with Turnover Intention at Private University in Malaysia - Fahmi, Nurul Irdina; Mohd, Idaya Husna; Ahmad, Nursaadatun Nisak; Noranee, Shereen; Abu Bakar, Syarifah Mastura Syed; Hoo, Wong Chee (Information Management and Business Review, 2024)
Employee turnover has long been acknowledged as a silent threat to any organization. The turnover phenomenon has been a highly pressing concern for private universities’ faculties. Despite the attentiveness and responsiveness of high rates of turnover around the globe, research on the area of turnover or turnover intention, as well as succession planning, career attitude and job security is limited. Past studies have not assessed the scale and nature of the association between these three variables. Thus, this study aims to explore the relationship between succession planning, career attitude and job security toward turnover intention. The study specifically focused on a private university in Malaysia and data was gathered through 148 questionnaire surveys. The conceptual framework developed consisted of dimensions of succession planning, career attitude, job security and turnover intention. A set of three hypotheses was developed that assessed whether there existed a positive or negative relationship between these three variables. For data analysis, the study utilized various numbers of statistical techniques such as exploratory factor analysis, confirmatory factor analysis, and cross-case analysis. The study results indicated that the research model developed was a good predictor of turnover intention and provided general support for all three hypotheses. The study also found that there was a positive relationship between succession planning, career attitude, and job security toward turnover intention. The empirical relationships between variables further proposed that it would be favorable and advantageous to the private university management to recuperate university turnover situations. Further discussions included the research contributions and implications.